(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article analyzes the essence and content of the amendments introduced to criminal legislation and the reforms implemented in recent years. It highlights measures aimed at the liberalization of criminal policy, the protection of human rights and freedoms, and the improvement of law enforcement practice. In particular, the expansion of elements of crimes, the criminalization of new types of offenses, and the modernization of certain legal norms are examined. The article also explores new forms of crime emerging in connection with the development of digital technologies, as well as issues related to their legal regulation. Furthermore, it analyzes key aspects of improving criminal legislation based on the experience of foreign countries. In addition, approaches aimed at the individualization of punishment, strengthening the principles of humanism, and the social rehabilitation of convicted persons are evaluated.